Enterococcus and Escherichia coli Like indicators of fecal pollution in coastal beaches of Lima - Vergaray, Germán (2007)
In July (winter) of 2005 and January (summer) of 2006 there was realized the microbiological study of the water of 8 beaches of summery recreation of the coast of Lima by the purpose of evaluating the usefulness of Escherichia coli and Enterococcus like indicators of fecal pollution. In every month 5 series of samplings were done. They used like indicators of fecal pollution total Coliforms (CT) 5,000 NMP/100mL, fecal Coliforms (CF) 1,000 NMP/100mL according to the Peruvian Norm and also to Escherichia coli (EC) 100 NMP/100mL and Enterococcus (E) 35 NMP/100mL. The results of the analyses realized in January qualify to the water of 3 beaches like unacceptable for the bath, according to the Peruvian Norm; but it is used as indicator EC and E, 8 beaches would be considered to be like unacceptable. The results of July demonstrate that the water of 8 beaches was acceptable, according to the Peruvian Norm, but it is used like indicators EC and E, 2 beaches would be considered like unacceptable. If we take in consideration that EC and E have major correlation with gastrointestinal diseases than CT and CF; we might affirm that EC and E are good indicators of fecal pollution for recreational waters of primary contact and they should be taken in consideration in a next review of the Peruvian Norm.